The growing phenomenon of smuggling and its impact on the national security of Algeria - Hamdi, Abderrahmane (Journal of Human Sciences, 2021)
Smuggling distinguishes itself from other forms of criminality by its characteristics and features that are due to its interaction with the circumstances, events and changes prevailing in the region which constitute a serious threat to national security of Algeria such as ongoing conflicts in the countries of the Sahel and the instability in Libya. Despite the fact that smuggling has economic roots as it is a reflection of the informal economy linked to illegal activities, its large-scale expansion has changed its nature becoming one of the greatest security threats facing Algeria mainly originating from the extreme South Sahara and the Sahel region as well as the eastern (Libya and Tunisia) and western (Morocco) borders. This change in the nature of smuggling is highlighted through the increase in the illegal trafficking of dangerous goods such as drugs and weapons which are imminent threats to the state security; a worsening which makes its containment harder. The structural link between smugglers and organized networks and terrorist groups has made smuggling a more complex and multidimensional crime (security, economic and social, etc.).